2002
DOI: 10.1073/pnas.242611099
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-specific chloride channel, OmClC-K, predominantly expressed in the diluting segment of freshwater-adapted tilapia kidney

Abstract: The kidney plays an important role in osmoregulation in freshwater teleosts, which are exposed to the danger of osmotic loss of Na ؉ and Cl ؊ . However, ion-transport mechanisms in the kidney are poorly understood, and ion transporters of the fish nephron have not been identified thus far. From Mozambique tilapia, Oreochromis mossambicus, we have cloned a chloride channel, which is a homologue of the mammalian kidney-specific chloride channel, ClC-K. The cDNA of the channel, named OmClC-K, encodes a protein wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
(32 reference statements)
2
36
1
Order By: Relevance
“…A much higher Na + /K + -ATPase activity has been revealed in the distal segments than in the proximal segments of freshwater fish, which suggests the involvement of those tubules in ion reabsorption (Petrova 1981). In the Mozambique tilapia, Oreochromis mossambicus, a percid species closely related to the sea bass, only the distal portions of the nephrons contain Na + /K + -ATPase when the fish is kept in freshwater (Miyazaki et al 2002). In seawater-maintained tilapias, however, no immunoreaction has been detected, an observation that reinforces our hypothesis of the osmoregulatory role of the collecting tubule/duct system.…”
Section: Discussionsupporting
confidence: 83%
“…A much higher Na + /K + -ATPase activity has been revealed in the distal segments than in the proximal segments of freshwater fish, which suggests the involvement of those tubules in ion reabsorption (Petrova 1981). In the Mozambique tilapia, Oreochromis mossambicus, a percid species closely related to the sea bass, only the distal portions of the nephrons contain Na + /K + -ATPase when the fish is kept in freshwater (Miyazaki et al 2002). In seawater-maintained tilapias, however, no immunoreaction has been detected, an observation that reinforces our hypothesis of the osmoregulatory role of the collecting tubule/duct system.…”
Section: Discussionsupporting
confidence: 83%
“…Very few studies have investigated ClCs in other fish species. In tilapia, ClC3 and -5 were cloned and found to be expressed in various organs including gills, but they were suggested to function as intracellular Cl -channels based on an in vitro functional analysis (Miyazaki et al, 2002). Recently, higher protein expression analysed by an anti-rat ClC3 antibody was found in FW pufferfish gills than in SW ones (Tang and Lee, 2007).…”
Section: Basolateral CL -Transportmentioning
confidence: 99%
“…Studies on the nephrons of trout, killifish, and other species have demonstrated distinct functional differences between the tubule segments (Braun and Dantzler 1997) and specific differential localization of transporters (Miyazaki et al 2002). Nishimura et al (1983) have shown that, in the distal tubule, chloride efflux (lumen to bath) is significantly higher than chloride influx (bath to lumen), suggesting the net Cl -reabsorption from the lumen to the bath and with a lumen-positive transepithelial voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of sodium in addition to chloride to generate the lumen-positive voltage in the distal tubule (Nishimura et al 1983) suggests the involvement of apical NKCC in Cl -reabsorption. The differential localization of transporters in teleosts include the cloning and characterization of a kidney-specific chloride channel, OmClC-K, cloned from tilapia (O. mossambicus; Miyazaki et al 2002); OmClC-K mRNA shows elevated transcript levels in FW-adapted tilapia compared with SW-adapted fish, whereas immunohistochemical evidence has revealed OmClC-K located in the basolateral membrane of the distal nephron suggesting that OmClC-K is involved in transepithelial Cl -reabsorption. In killifish, Cliff and Beyenbach (1992) have reported similarities in the in vitro functional properties of secretory proximal tubules by using isolated SW-and FW-adapted proximal tubules.…”
Section: Introductionmentioning
confidence: 99%